PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM MAKMUR JAYA KOTA PROBOLINGGO - Punky Praja Jatmika; Mohammad Bayu Dasril Sriadi (LP2M Universitas Bina Bangsa, 2022)
This research aims to examine the effect of compensation on employee performance in The Save and Borrow Makmur Jaya Cooperative in Probolinggo City. Quantitative research is the type of research used. The research population is all employees of Simpan Pinjaman Makmur Jaya Cooperative numbering 32 people and all populations are sampled as many as 32 people through the use of census methods. The data collection technique is observing, documentation, and giving questionnaires. In analyzing the data by conducting tests of validity, reliability, determination coeffesiency, simple linear regression, and hypothesis testing with partial significance testing (statistical t test). Based on the analysis of data showing variable compensation and employee performance in Makmur Jaya Cooperative Kota Probolinggo which is shown through testing the validity of the calculating value exceeds the table value of 0.349 (valid), reliability testing obtained all variables indicate reliability value that exceeds reliability standard 0.60, simple linear regression testing. Y = 3,706 + 0.549 (X) has a positive value, the coefficient of determination is 0.432, and the hypothesis test obtained a calculated value exceeding a ttabel that has a significance of less than 0.05. The coefficient of determination is obtained a value of 0.432 or 43.2%. Thus it can be mentioned that 43.2% of employee performance in Makmur Jaya Cooperative of Probolinggo City is affected by Compensation. Meanwhile, 56.8% of it is the influence of other aspects that are not studied